The War Ethics in the Light of Islam and International Humanitarian Law (IHL): A Research Based Comparative Review - Hafsa Nawaz; Dr. Kaleem Ullah (Journal of Religion and Society, 2026)
Sustained and continuous confrontation between two sovereign states for the achievement of ideological, political, social or economic interests using organized military forces and their deployment for the subject causes may be referred to as war. To pursue the said objectives or causes, the opponents may often pursue unlawful, unethical or any other means that adversely affect the established principles, laws, norms, rules or regulations therein undermining the social and global peace. In order avert the ongoing practices and intensify efforts for the accomplishment of peace, ethical framework and legal regulations have been proposed and recently developed, which themselves are subject to modifications and interpretations governing war and warfare. These regulations are often disregarded, ignored, and overlapped by the two confronting states, without acknowledging the negative consequences. Islam is a religion of peace and harmony that always curses and discourages any use of warfare. In extreme circumstances where disorder, corruption and injustice are reportedly being spread by any individual, group or any sovereign state, Islam permit and direct its followers towards intense armed struggle which is only meant for the self-defense and establishment of peace, security and justice and social harmony. Furthermore, the ethical principles and legal regulations of warfare duly established 14 centuries ago by teaching of Islam and Sunnah remained the same and unchanged that could be found in its original essence. Keywords: War Ethics, Islam, International Humanitarian Law, Peace, Legal Regulation